The diversity of legal institutions and traditions of Kazakhs (XVIII–XIX centuries) - Balabiyev, K.R. (Bulletin of the Karaganda University “Law Series”, 2019)
In the article various forms of legal traditions and institutions of Kazakhs, the court of aksakals, arbitration courts, coexisted along with the biys courts, which have become independent and alternative legal methods were considered. These courts were random in their legal status, but preserved as an independent legal institution, where simple rituals were the instrument of social obligations and determined the scope of actions and standards of conduct for each participant. It is necessary to accept the history in all its versatility, to consider more deeply the relationship between the legal traditions of Shariat and Adat in the structure of the biys court. The main provisions of the work are based on the theory of legal diversity, the works of Kazakh and Russian authors on the problems of Kazakh customary law, as well as some English-language studies. Address to this problem is caused by the urgent need for the publication of documents that can provide a complete and accurate reconstruction of the forms of the legal culture of the Kazakhs and ethical standards, which could be an effective tool in shaping and adhering to the principles and ethics of relationships within society. The results of the study make it possible to substantiate their own approach based on a combination of historical, legal, anthropological and culturological approaches. In the light of the historically important events that have taken place in recent years, we are faced with the task of studying the legal institutions of the Kazakhs, the norms of customary law for possible application in resolving conflicts, reconciling the parties and reviving the moral values of the Kazakh people.